Enthesopathy in spondyloarthritis: the literature review - D. I. Abdulganieva; E. R. Kirillova; I. F. Fairushina; G. R. Gaynullina; R. Z. Abdrakipov; R. G. Mukhina; E. I. Mukhametshina (Научно-практическая ревматология, 2021)
The article presents data on epidemiology, pathogenesis, clinical manifestations, diagnosis and therapy of enthesopathy in spondyloarthritis. The approaches to assessment of this pathology are examined and detailed, modern clinical and ultrasound indices are given. The features of enthesopathy in diseases that included in the group of spondyloarthridies are described.